Analysis of Increasing Flash Flood Frequency in the Densely Urbanized Coastline of the Campi Flegrei Volcanic Area, Italy - Esposito, Giuseppe; Matano, Fabio; Scepi, Germana (Frontiers in Earth Science, 2018)
Climate change is affecting the frequency and severity of extreme meteorological and geo-hydrological events hitting the coastal zone of the Campi Flegrei volcanic district (southern Italy), which is prone to a wide spectrum of natural hazards, including volcanism, earthquakes, ground deformation, flash floods, landslides and coastal erosion. This study documents the trend of flash floods affecting the urban area of Pozzuoli, located along the coastline of the Campi Flegrei volcanic area during 1970-2014 time period. An archive research together with the collection of data published on news websites and social media allowed understanding of the triggering and evolution mechanisms of flash floods in the area, as well as the most recurrent damages. Rainfall data collected by the rain gauge located within the Pozzuoli watershed were also analyzed and rainfall properties estimated. Results of this study show an increased frequency of flash flood events occurred in the study area. The variation in flash flood frequency is likely not related to urbanization changes, as no increase of the urban area occurred after the year 2000. The observed increase in the flash flood events in recent years (2000-2014) can be reasonably ascribed to variations in the rainfall regime. Our research provide a contribution for the understanding of flash flood processes in the study area as well as relevant information for hazard and risk assessment.